OPTIMALISASI MEDIA PENJUALAN ONLINE SEBAGAI SALAH SATU STRATEGI PEMASARAN PRODUK KOPERASI TENUN PANDAI SIKEK - Rahmi Eka Putri; Rian Ferdian; M. Hafiz Hersyah; Nefy Puteri Novani; Ratna Aisuwarya; Ricky Akbar (LPPM Universitas Andalas, 2020)
The Community Service Activities were carried out at the Koperasi Tenun Pandai Sikek located in Nagari Pandai Sikek Kecamatan X Koto Kabupaten Tanah Datar. Koperasi Tenun Pandai Sikek is a cooperative with weavers originating from Nagari Pandai Sikek. The products marketed by the cooperative are in the form of Pandai Sikek woven cloth and several West Sumatran handicrafts. The marketing model used today is still conventional, where potential buyers who want to buy products must come directly to the cooperative which makes access to product marketing limited. The development of information technology now allows product marketing to be done through online marketing media to increase sales. This service activity aims to provide training and assistance to members of the Koperasi Tenun Pandai Sikek in optimizing online marketing media as one of the product marketing strategies so that Pandai Sikek woven fabric and handicrafts typical of West Sumatra can be introduced and marketed not only in the area of origin but also in scale national and international. The method of implementing the activity was carried out in three stages, namely the initial survey, training on online marketing media and the assistance of cooperative members in the use of online marketing media. In this activity, used one of the online sales sites, namely Tokopedia At present, the product of Pandai Sikek Cooperative has been marketed online through tokopedia's sales site at https://www.tokopedia.com/pandai-sikek